The Linked Response: Lessons Emerging from Integration of HIV and Reproductive Health Services in Cambodia. (31st January 2013) - White, Joanna; Delvaux, Thérèse; Chhea, Chhorvann; Saramony, Sarun; Ouk, Vichea; Saphonn, Vonthanak
Abstract : A qualitative assessment was made of service provider and user perceptions of the quality of integrated reproductive health services established through a pilot intervention in Cambodia. The intervention aimed to promote pregnant women's HIV testing and general utilization of reproductive health facilities as well as improve the follow-up of HIV-positive women and exposed infants through strengthened referral and operational linkages amongst health facilities/services and community-based support interventions for PLHIV. The study was conducted in one operational district where the intervention was piloted and for comparative purposes in a district where integrated services had yet to be implemented. Service providers in the pilot district reported improved collaboration and coordination of services, more effective referral, and the positive impact of improved proximity of HIV testing through integrated local level facilities. Community-based support teams for PLHIV embraced their expanded role, were valued by families receiving their assistance, and were understood to have had an important role in referral, PMTCT follow-up and countering PLHIV stigmatization; findings which underscore the potential role of community support in integrated service provision. Challenges identified included stigmatization of PLHIV by health staff at district hospital level and a lack of confidence amongst non-specialized health staff when managing deliveries by HIV-positive women, partly due to fear of HIV transmission.